The New Dining Practice Standards: Speech-Language Pathologists' Guide to Their Implementation - Bowman, Carmen (Seminars in Speech and Language, 2013)
In 2010, the “Creating Home II National Symposium on Culture Change and the Food and Dining Requirements” cosponsored by Centers for Medicare and Medicaid services (CMS) and the Pioneer Network created a multidisciplinary task force for dining practice standards. In 2011, this task force crafted and finalized the New Dining Practice Standards. These standards have been agreed upon by 12 national clinical standard setting organizations and will be referred to by CMS as new standards of practice. The new standards include evidence-based research, as well as new thinking in advance of research and corroboration with federal requirements. Speech-language pathologists can guide care communities in implementing the new standards and lead a new era of honoring the person in making informed decisions and mitigating risk of harm at the same time.
Keywords: Dining; standards; food; older population; clinical standards